Functional Outcome Assessment of The Knee Joint After Anterior Cruciate Ligament Reconstruction - Roy, SK; Debnath, S; Mahara, DP; Kairy, RR (Bangladesh Medical Journal, 2014)
Anterior Cruciate Ligament injury is a common problem, frequently requires reconstruction especially for the young and active patient. Post operative assessment is mandatory for the demanding patients. There are different types of rehabilitation protocol including timing, range of motion, muscles strength, stability, proprioception, agility test (functional test) and scoring system. Here we used Lysholm and Gillquest knee score. In our study we include only 10 patients because we got total documentations for those patients only; we got normal function (95-100) in one case, near normal (84-94) in 9 cases and none of those fall in abnormal (< 84) category. We conclude that scoring assessment well correlates with the functional outcome. DOI: http://dx.doi.org/10.3329/bmj.v41i2.18805 Bangladesh Medical Journal 2012 Vol. 41 No. 2: 40-44